Shade and NPK Effects on Calliandra and Sengon Seedling Growth Differences - Rumondang, Jenny; Ratna Puri, Suci; Rif’atunaudina, Ria; Handayani, Rajjitha; Hardiyanti, Rizky Ayu; Dinanty, Fawwaz (Jurnal Biologi Tropis, 2025)
Calliandra (Calliandra sp.) is a shrub with multiple benefits, including its use as firewood and as a high-protein livestock feed. Sengon (Paraserianthes falcataria) is a fast-growing tree species widely cultivated to support the timber industry. To enhance seedling growth and productivity, environmental manipulation through shading and fertilization is necessary. This study aims to evaluate the effects of shading and NPK fertilizer doses on the growth of Calliandra calothyrsus and Sengon seedlings in the context of industrial forest plantation management. Using a completely randomized design, this study tested four shading levels (no shading, 25%, 50%, and 75%) and four NPK fertilizer doses (0, 1, 2, and 3 g per seedling). Each treatment was repeated twice, resulting in a total of 248 seedlings per species. The observed variables included height, diameter, and leaf count. The results showed that Calliandra exhibited no significant differences in height growth across shading levels. However, the best growth was observed under 25% shading, with a height increase of 11.84 cm and a diameter of 1.55 mm, and at an NPK dose of 2 g, with a height of 10.75 cm and a diameter of 1.54 mm. Meanwhile, Sengon showed the best height growth under 75% shading with an NPK dose of 1 g per seedling. The optimal diameter growth for Calliandra was achieved under 25% shading with an NPK dose of 1 g, while Sengon exhibited the best diameter growth without shading and with an NPK dose of 3 g.